Intrinsic role of chaperone-mediated autophagy in cancer stem cell maintenance. Issue 12 (2nd December 2022) - Auzmendi-Iriarte, Jaione; Matheu, Ander
ABSTRACT: Chaperone-mediated autophagy (CMA) is a selective type of autophagy specialized in the individual degradation of targeted proteins. Its impact in any cancer stem cell (CSC) subtype remained elusive. In a recent study, we characterized the expression of LAMP2A and CMA activity in glioblastoma revealing its enrichment in a glioma stem cell (GSC) subpopulation. LAMP2A downregulation diminishes proliferation and self-renewal and induces apoptosis in GSCs in vitro, whereas it delays tumor progression in vivo . The underlying molecular signature of CMA comprises several proteomic and transcriptomic pathways with special relevance to mitochondrial function, the interferon pathway and extracellular matrix interactions. Remarkably, these activities are translated into the clinical scenario, as glioblastoma (GBM) samples show increased expression of LAMP2 compared to healthy tissue, with this expression being positively associated with malignancy grade, TMZ resistance and lower patient survival. These results reveal a novel function of CMA as an intrinsic regulator of GSC tumorigenic properties and highlight its relevance in GBM progression.